Dental pulp stem cells and their characterization - Suchanek, Jakub; Soukup, Tomas; Visek, Benjamin; Ivancakova, Romana; Kucerova, Lenka; Mokry, Jaroslav (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2009)
AIMS: Our aims were to isolate dental pulp stem cells, to cultivate them in various media and to investigate their basic biological properties and phenotype. METHODS: 16 lines of dental pulp stem cells (DPSCs) were isolated from an impacted third molar. After enzymatic dissociation of dental pulp, DPSCs were cultivated in modified cultivation media for mesenchymal adult progenitor cells containing 2 % or 10 % fetal calf serum (FCS), or in modified 2 % FCS cultivation media supplemented with ITS. Cell viability and other biological properties were examined periodically using a Vi-Cell analyzer and Z2-Counter. DNA analysis and phenotyping were done using flow cytometry. RESULTS: We were able to cultivate DPSCs in all tested cultivation media over 40 population doublings. Our results showed that DPSCs cultivated in medium supplemented with ITS had shorter average population doubling time (24.5, 15.55-35.12 hours) than DPSCs cultivated in 2 % FCS (55.43, 21.57-187.14 hours) or 10 % FCS (42.56, 11.86 - 101.3 hours). Cell diameter was not affected and varied from 15 to 16 microm. DPSCs viability in the 9(th) passage was over 90 %. Our phenotypical analysis was highly positivity for CD29, CD44, CD90 and HLA I, and negative for CD34, CD45, CD71, HLA II. DPSC lines cultivated in all media showed no signs of degeneration or spontaneous differentiation during the expansion process. CONCLUSIONS: We showed that ITS supplement in the cultivation media greatly increased the proliferative activity of DPSCs. Other DPSC biological properties and phenotype were not affected.
Keywords: zubní dřeň; Humans; Antigens, CD; lidé; Phenotype; proliferace buněk; mladý dospělý; Female; fenotyp; Cells, Cultured; Male; Dental Pulp; kmenové buňky; Stem Cells; Adult; dospělí; CD antigeny; kultivační média; Cell Proliferation; Culture Media; kultivované buňky; ženské pohlaví; mužské pohlaví; Young Adult